Penyimpangan Sanksi Pidana Terhadap Percobaan Dalam Undang-Undang Tindak Pidana Pencucian Uang Dengan KUHP - Dharma, Kadek Dwima Cipta; Yudiantara, I Gusti Ngurah Nyoman Krisnadi (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 9 (2024), 2025)
The goal of this writing is to determine whether deviations can be made regarding criminal sanctions for attempted money laundering offenses within the provisions of general criminal law and to elucidate the position of regulations concerning money laundering offenses that deviate from the general criminal law regulations within the legislative framework of Indonesia. This writing employs a normative research method that addresses norm conflicts. The findings of this writing indicate that deviations in the regulations governing money laundering offenses from the general criminal law regulations regarding sanctions for attempted crimes are permissible. This is based on the principle of preference, one of which is the lex specialis derogat legi generalis principle, as well as the existence of provisions in the general criminal law regulations that allow for such deviations. Despite these deviations, the regulations remain valid and maintain their position as one of the legislative regulations in Indonesia.